The situation of women in the agribusiness sector in Africa. Issue 6 (18th August 2017) - Adam, Rahma Isaack; Osano, Philip; Birika, Joan; Ndede Amadi, Atieno A.; Bwisa, Henry
ABSTRACT: This practical note syntheses the proceedings of a gender forum on women in agribusiness, which took place in Nairobi, Kenya in April 2015. The workshop session of the forum focused on two themes: financing options and entrepreneurship capacities. The public session covered six main areas: (1) post-harvest food management, (2) policies to enhance affirmative action, (3) regional integration and international trade, (4) technologies, (5) land and water management for agriculture, and (6) the next generation of agribusiness entrepreneurs. The multi-sectoral forum brought together some key stakeholders across East Africa to share experiences and best practices, increase mutual learning, and expand public discourse on the subject.